Mesocomposites Based on the Polymethylmethacrylate Matrix - Novotný, Jan; Jaskevič, Martin; Lysoňková, Irena (Manufacturing Technology Journal, 2018)
This article describes the formation of a composite coating in a polymer matrix on an aluminum alloy. It is a PMMA coating (polymethylmethacrylate) with the addition of TiO2 particles. Working with these particles requires not only safety but also a suitable preparation process to obtain particles of suitable size, their subsequent homogeneous distribution in the coating (particles of this size are influenced by electrostatically attractive forces and have a strong tendency to aggravate). The first part describes the material used, sample preparation and coating process, surface roughness measurement, SEM and EDS analysis of selected samples. The aim of the research is to find out whether it is possible to use dipping and brushing techniques when coating Al-Si alloys with polymeric materials. Consequently, what can be achieved is the roughness of the surface of the coated part compared to the uncoated surface (at different particle concentrations in the spin) and the distribution of TiO2 particles on the surface of the sample.
Keywords: Mesoparticles; coating; TiO2; PMMA; surface roughness